Trends and factors associated with the nutritional status of adolescent girls in Ghana: a secondary analysis of the 2003–2014 Ghana demographic and health survey (GDHS) data. Issue 7 (6th July 2022) - Azupogo, Fusta; Abizari, Abdul-Razak; Aurino, Elisabetta; Gelli, Aulo; Osendarp, Saskia JM; Bras, Hilde; Feskens, Edith JM; Brouwer, Inge D
Abstract: Objective: We examined the trends over time and the factors associated with malnutrition among adolescent girls in Ghana. Design: Cross-sectional analysis from 3 nationwide Ghana Demographic and Health Surveys conducted in 2003 ( n 983), 2008 ( n 955) and 2014 ( n 857). We used Cox proportional hazard models with sample weighting to model the prevalence ratio (PR) of malnutrition. Setting: Countrywide, covering rural and urban areas in Ghana. Participants: Non-pregnant adolescent girls aged 15–19 years. Results: Compared with 2003, thinness declined marginally (PR 0·88 (95 % CI 0·45, 1·73)) in 2008 and in 2014 (PR 0·71 (95 % CI 0·38, 1·56)). Stunting declined marginally by 19 % in 2008 (PR 0·81 (95 % CI 0·59, 1·12)), flattening out in 2014 (PR 0·81 (95 % CI 0·57, 1·17)). We found an increasing trend of overweight/obesity with the PR peaking in 2014 (PR 1·39 (95 % CI 1·02, 1·88)) compared to 2003. The anaemia prevalence remained severe without a clear trend. A low level of education of the adolescent girl was positively associated with stunting. Increasing age was positively associated with stunting but inversely associated with thinness and anaemia. Girls who ever bore a child were more likely to be anaemic compared to those who never did. A lower level of household wealth and a unit increase in household size was negatively associated with overweight/obesity. Urban dwelling girls were less likely to be stunted. Conclusions: The stagnant burden of under-nutrition and rising over-nutrition emphasise the need for double-duty actions to tackle malnutrition in all its forms in Ghanaian adolescent girls.